Lugusid materjalidest = Stories about materials - Jõeste, Kristi; Adang, Richard; Kaaristo, Maaria; Parts, Priit-Kalev; Rennu, Madis (Studia vernacula, ISSN 1736-8138, 2013)
Summaries in English.
Keywords: aineellinen kulttuuri; ben (vävnader); bruksföremål; byggnadsarv; garvning; hantverkstradition; kasvikuidut; kivirakennukset; kivirakenteet; kudonta; kulttuuriperintö; kulturarv; käsityöperinne; käyttöesineet; luu; läderarbeten; materiell kultur; nahkatyöt; parkitus; puurakennukset; puurakentaminen; rakennusperintö; rökbastur; savusaunat; stenbyggnader; stenkonstruktioner; träbyggande; träbyggnader; tupasvilla; tuvull; villapaidat; vävning; växtfibrer; ylletröjor; Estland; Finland; Itämeren alue; Suomi; Viro; Östersjöområdet